2015
DOI: 10.1089/end.2015.0260
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Practice Patterns of Flexible Ureteroscopy for Treating Renal Stones: Results of a Worldwide Survey

Abstract: The overwhelming majority of endourologists surveyed consider fURS as a first-line treatment modality for renal stones, especially those <2 cm. Use of UAS, high-power holmium lasers, and dusting technique has become popular among practitioners. When defining stone free after fURS, the majority of endourologists used a zero fragment or RF <2 mm definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 23 publications
4
74
1
1
Order By: Relevance
“…However, because of the lack of an established standard, the choice of stents for the treatment of ureteral stones is often a matter of surgical preference and experience. A survey carried out last year showed that 63% of the surgeons still routinely stented patients following URL [38]. Although ureteral stents are used differently in ESWL and URL, the function and purpose are similar.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the lack of an established standard, the choice of stents for the treatment of ureteral stones is often a matter of surgical preference and experience. A survey carried out last year showed that 63% of the surgeons still routinely stented patients following URL [38]. Although ureteral stents are used differently in ESWL and URL, the function and purpose are similar.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are important in the context of the increasing use of flexible ureteroscopy, especially for larger renal stones. 23,24 In fact, investigators have suggested that ureteroscopy may indeed be the treatment of choice for obese patients with renal stones based on perceived …”
Section: Discussionmentioning
confidence: 99%
“…Improvement of the instruments as well as endoscopic technology has made flexible ureteroscopy (fURS) as an increasingly popular treatment option for patients with renal stones (Ghani & Wolf, 2015; Dauw et al, 2015; Wang & Preminger, 2011). Indication for fURS also has been extended, even for stone larger than 2 cm (Aboumarzouk et al, 2012; Breda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%